PENGARUH TIME BUDGET PRESSURE, PROFESIONALISME, DAN FEE AUDIT TERHADAP KUALITAS AUDIT - Rafif Helmi Fauzan (2021)
This study aims to examine the effect of time budget pressure, profesionalism, and audit fee on quality of audit. The sample used in this study was an auditor that work at public accounting firm in Jakarta. Sampling was carried out using a physical and digital questionnire. Total of the sample that has been collected was 75 respondents. The data analysis used in this study was PLS program or Partial Least Square with a significant level of 5%. The results of this study indicate that (1) Time Budget Pressure has a significant effect on Audit Quality, (2) Profesionalism has a significant effect on Audit Quality, (3) Audit Fee has a significant effect on Audit Quality.